PERFORMANCE IMPLICATION OF KNOWLEDGE MANAGEMENT PROCESS AT PT INDO HARAPAN MAKMUR MANADO - Damar, Giofanni .; Pangemanan, Sifrid .; Worang, Frederick G. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract : The purpose of this study is to analysis performance implication of knowledge management process at PT Indo Harapan Makmur Manado. This research is using qualitative research method that explores the theories from several journal, articles, book and previous research. The type of this research is descriptive research. Descriptive qualitative approach used in this research describes and explore the knowledge management process at PT Indo Harapan Makmur Manado. Population in this qualitative research is employee in PT Indo Harapan Makmur Manado that can be respondent about this issues. The result of this research is where the company has applied knowledge management and the process, but from each informant said that the application of the knowledge management process is not too maximal and directed, in the case of the company is a family company, so the process in it is only studied in writing. Company must apply the management of knowledge in the company must be maximized; because of this knowledge management is very important in running each business and will not lose competition with other distributor companies.Â Keywords: knowledge management and knowledge management process